The parerigonine genus Paropesia Mesnil (Diptera, Tachinidae), with descriptions of three new species from East Asia - Shima, Hiroshi (Zootaxa, 2014)
Three new species of Paropesia Mesnil (Phasiinae, Parerigonini) are described: P. discalis sp. nov. from China and Myanmar, P. grisea sp. nov. from Japan and P. tessellata sp. nov. from Myanmar and China. The type species of Paropesia, P. nigra Mesnil, is redescribed. The male and female terminalia of the new species are described and illustrated and characteristics of the genus Paropesia are briefly discussed.